2020
DOI: 10.1186/s12960-020-00477-9
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a health video library for use in Afghanistan: provider-level acceptability and lessons for strengthening operational feasibility

Abstract: Background: Community health workers (CHWs) in Afghanistan are a critical care extender for primary health services, including reproductive, maternal, neonatal, and child health (RMNCH) care. However, volunteer CHWs face challenges including an ever-expanding number of tasks and insufficient time to conduct them. We piloted a health video library (HVL) intervention, a tablet-based tool to improve health promotion and counseling by CHWs. We qualitatively assessed provider-level acceptability and operational fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
(39 reference statements)
0
11
0
Order By: Relevance
“… 10 Clinical efficiency, cost-effectiveness, and improved treatments are some of the benefits of Virtual Communication technologies. Nurses working in rural areas may contact experienced urban nurses through Virtual Communication technologies to seek advice that may help to decrease their workload 34 Lack of Virtual Communication training could increase nursing workload. 10 50% of Virtual Communication technologies showed positive reduction in the workload of nurses 34 , 35 and 50% described an increase.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 10 Clinical efficiency, cost-effectiveness, and improved treatments are some of the benefits of Virtual Communication technologies. Nurses working in rural areas may contact experienced urban nurses through Virtual Communication technologies to seek advice that may help to decrease their workload 34 Lack of Virtual Communication training could increase nursing workload. 10 50% of Virtual Communication technologies showed positive reduction in the workload of nurses 34 , 35 and 50% described an increase.…”
Section: Resultsmentioning
confidence: 99%
“…40% of the articles found that providing proper education and upgrading the knowledge of nurses and the target population were fundamental facilitators for the technology use by nurses. 5 , 11 , 14 , 16 - 18 , 22 , 24 , 26 , 29 , 30 , 34 , 37 , 39 , 40 Mills et al 22 highlighted proper training as a facilitator of computer use by nurses especially in rural areas where training opportunities are more scarce than in urban areas. To reduce workload efforts, nurses must receive sufficient training to use the technology as to limit the amount of additional time necessary for self-learning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that mobile ICTs can improve the performance of CHAs in their ability to perform health promotion, collect and report timely information regarding family health, provide health services such as vaccines, and refer families to appropriate local health services (3,(47)(48)(49)(50)(51)(52)(53). Additionally, when a mobile ICT tools are used by a CHA, the device can increase the confidence the caregivers have in the messages being transmitted and increase the confidence the CHAs have in their own work (47,48,51,52,(54)(55)(56). Through implementation science, innovations in mobile ICTs and strategies for child health and development can be extended to low resource settings to empower local actors and spread the benefits of advancements in technology (3,50).…”
Section: Exploration Stage: Identifying Challenges and Solutionsmentioning
confidence: 99%